Physiological Amputation of Limb (Limb Gangrene) after Tourniquet Application for 12 days following Snake Bite - Yadav, Ashok Kumar; Bhandari, R.; Agrahari, A.K.; Gupta, R.; Shah, M.K. (Journal of BP Koirala Institute of Health Sciences, 2018)
Background: Application of tourniquet and herbs has been practiced since a long time in patients with different reptiles’ and arthropods’ bite at rural areas of the country, despite various cases of cellulitis and gangrene. Objective: To report a case of limb gangrene following tourniquet and herb application for snake bite. Case: A 20-years old farmer, who was bitten by a snake, presented to the Emergency department with complaints of blackish discoloration of his left forearm and hand. After clinical evaluation and investigations, patient underwent surgical intervention. Twelve days following snake bite, patient felt pain, noticed bleeding from bite site, swelling over his left hand, palpitation, shortness of breath and inability to speak. For which, he sought help from a traditional healer who applied a tourniquet over his left elbow and some herbs over the bite site. He noticed blackening of his fingers, which rapidly progressed to involve his left hand and forearm up to the site of tourniquet. He underwent surgery for the gangrenous limb. Conclusion: Development of gangrene following tourniquet is an unusual finding in modern day medicine. This case report shows the danger related to tourniquet application and need for measures to prevent such incidents in future.